2020
DOI: 10.1111/hex.13016
|View full text |Cite
|
Sign up to set email alerts
|

Communicating cancer risk in the primary care consultation when using a cancer risk assessment tool: Qualitative study with service users and practitioners

Abstract: Background Cancer risk assessment tools are designed to help detect cancer risk in symptomatic individuals presenting to primary care. An early detection of cancer risk could mean early referral for investigations, diagnosis and treatment, helping to address late diagnosis of cancer. It is not clear how best cancer risk may be communicated to patients when using a cancer risk assessment tool to assess their risk of developing cancer. Objective We aimed to explore the perspectives of service users and primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 46 publications
(98 reference statements)
1
31
0
1
Order By: Relevance
“…Six studies in our review provided information about why primary care physicians decide whether to communicate diagnostic uncertainty ( 2 , 16–18 , 28 , 30 ). Time constraints as a barrier to communicating information about diagnostic uncertainty were discussed ( 18 ), as was the perception that patients are intolerant of uncertainty ( 24 ), preferring ‘ black and white answers ’ ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies in our review provided information about why primary care physicians decide whether to communicate diagnostic uncertainty ( 2 , 16–18 , 28 , 30 ). Time constraints as a barrier to communicating information about diagnostic uncertainty were discussed ( 18 ), as was the perception that patients are intolerant of uncertainty ( 24 ), preferring ‘ black and white answers ’ ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…In two of the studies identified, the importance of communicating about diagnostic uncertainty was discussed in the context of the principles of openness and honesty: physicians emphasized the importance of such communication in managing patient expectations ( 28 ) and building trust ( 28 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As these tools have not been widely adopted to date, a UK research team recently sought to explore the perspectives of patients and clinicians on their use in communicating cancer risk information. 3 Participants suggested ways to improve communication: personalising risk information; involving patients in use of the tool; sharing risk information openly; and providing sufficient time when using the tool during consultations. It is the last of these that I suspect is most critical, and frustratingly, is probably also the most challenging to ameliorate in the current healthcare climate.…”
mentioning
confidence: 99%